2012
DOI: 10.1271/bbb.120006
|View full text |Cite
|
Sign up to set email alerts
|

Effective Cytochrome P450 (CYP) Inhibitors Isolated from Tarragon (Artemisia dracunculus)

Abstract: Two effective cytochrome P450 (CYP) inhibitors were isolated from tarragon, Artemisia dracunculus. Their structures were spectroscopically identified as 2E,4E-undeca-2,4-diene-8,10-diynoic acid isobutylamide (1) and 2E,4E-undeca-2,4-diene-8,10-diynoic acid piperidide (2). Both compounds had dose-dependent inhibitory effects on CYP3A4 activity with IC 50 values of 10:0 AE 1:3 M for compound 1 and 3:3 AE 0:2 M for compound 2, and exhibited mechanism-based inhibition. This is the first reported isolation of effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Brahmi et al () tested Neopellitorine A ( 39 ) and Neopellitorine B ( 40 ) against P450 (CYP) inhibition where both compounds 39 and 40 exhibited mechanism‐based and dose‐dependent inhibition of CYP3A4 activity with IC 50 10.0 ± 1.3 and 3.3 ± 0.2 μM, respectively. Inhibition of CYP450 is pharmacologically very important as it is a major factor interacting with a drug after its administration altering their pharmacokinetics and response.…”
Section: The Chemistry and Pharmacology Of Artemisia Alkaloids/alliedmentioning
confidence: 99%
“…Brahmi et al () tested Neopellitorine A ( 39 ) and Neopellitorine B ( 40 ) against P450 (CYP) inhibition where both compounds 39 and 40 exhibited mechanism‐based and dose‐dependent inhibition of CYP3A4 activity with IC 50 10.0 ± 1.3 and 3.3 ± 0.2 μM, respectively. Inhibition of CYP450 is pharmacologically very important as it is a major factor interacting with a drug after its administration altering their pharmacokinetics and response.…”
Section: The Chemistry and Pharmacology Of Artemisia Alkaloids/alliedmentioning
confidence: 99%
“…In addition, some regional varieties of tarragon are distinguished by their essential oil content [1,15,16]. The principal seconder metabolites of A. dracunculus L. are pyhtoalexins, coumarins, chromones, phenylpropanoids, phenylpropenes, chalcones, alkamides, polyphenolics, acetylenes, monoterpenes alkamides, flavonoids and sesquiterpene lactones [17][18][19][20][21][22][23]. The marker compound in the composition of A. dracunculus L. leaves is reported as herniarin [24].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the MBI of human CYPs by constituents isolated from traditional herbal medicines [27,28,29]. For the TDI assessment with H. helix extracts, IC 50 shifts were calculated by comparing IC 50 vales from the co-incubation assay to the pre-incubation assay [17], which showed positive results (≥1.5) for CYP2C8 and CYP2C19.…”
Section: Discussionmentioning
confidence: 99%